1998
DOI: 10.1023/a:1022586221077
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: rFSH is more efficacious than urinary HP-FSH for ovulation induction in WHO group II anovulatory infertile patients as assessed by follicular development, hormonal levels, and the amount of FSH required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This preference was noticed in other studies [ 9 , 15 , 25 , 36 ] without finding any significant improvement on clinical outcomes. Indeed, as demonstrated in our study, there was no significant difference between different protocols used for COS (rFSH/Gonal-F; rFSH/Puregon; uFSH/Fostimon; and hMG/Menopur; Table 2 ), although, in contrast, some authors pointed to the greater potency of rFSH [ 22 , 48 ]. However, other studies have reported higher pregnancy rates for hMG [ 33 , 49 53 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This preference was noticed in other studies [ 9 , 15 , 25 , 36 ] without finding any significant improvement on clinical outcomes. Indeed, as demonstrated in our study, there was no significant difference between different protocols used for COS (rFSH/Gonal-F; rFSH/Puregon; uFSH/Fostimon; and hMG/Menopur; Table 2 ), although, in contrast, some authors pointed to the greater potency of rFSH [ 22 , 48 ]. However, other studies have reported higher pregnancy rates for hMG [ 33 , 49 53 ].…”
Section: Discussionsupporting
confidence: 58%
“…Generally, rFSH is commonly used to minimize the possibility of developing ovarian cysts associated with LH contamination and to improve the probability of a more consistent, effective, and efficient ovarian response [ 22 , 48 ].…”
Section: Discussionmentioning
confidence: 99%